Role of gut microbiota on intestinal barrier function in acute pancreatitis - Li, Xue-Yang; He, Cong; Zhu, Yin; Lu, Nong-Hua (World journal of gastroenterology : WJG, 2020)
Acute pancreatitis (AP) is a common gastrointestinal disorder. Approximately 15%-20% of patients develop severe AP. Systemic inflammatory response syndrome and multiple organ dysfunction syndrome may be caused by the massive release of inflammatory cytokines in the early stage of severe AP, followed by intestinal dysfunction and pancreatic necrosis in the later stage. A study showed that 59% of AP patients had associated intestinal barrier injury, with increased intestinal mucosal permeability, leading to intestinal bacterial translocation, pancreatic tissue necrosis and infection, and the occurrence of multiple organ dysfunction syndrome. However, the real effect of the gut microbiota and its metabolites on intestinal barrier function in AP remains unclear. This review summarizes the alterations in the intestinal flora and its metabolites during AP development and progression to unveil the mechanism of gut failure in AP.